Endoscopic radial incision and cutting for Crohn’s Disease-associated intestinal stricture: a pilot study - Moroi, Rintaro; Shiga, Hisashi; Kuroha, Masatake; Kanazawa, Yoshitake; Nochioka, Kotaro; Kakuta, Yoichi; Kinouchi, Yoshitaka; Masamune, Atsushi (Endoscopy International Open, 2020)
Background and study aims Intestinal stricture associated with Crohn’s disease (CD) is usually treated by endoscopic balloon dilation (EBD) or stricture plasty. Although EBD is effective and safe for such strictures, refractory stricture after EBD poses a problem. Hence, other novel approaches for these refractory strictures are required. On the other hand, the efficacy of radial incision and cutting (RIC) method for esophageal stricture after esophagogastric surgery is reported. In this pilot study, we adopted the RIC technique for five CD patients with refractory intestinal stricture to dilate their strictures. We conducted the RIC procedure using an electric needle knife with a ceramic tip on the top of the needle. Four cases were of anastomotic stricture after ileocecal resection and the remaining one case was of stricture due to mucosal healing. The RIC procedure was successful for all five patients. Average procedure time was 18.6 minutes. One patient developed delayed bleeding after RIC. There were no cases of perforation. RIC could be an alternative therapy for intestinal stricture associated with CD. Further studies should be conducted to clarify its efficacy and safety.